Polyester composite film as well as preparation method and application thereof

By introducing polyhydroxy monomers and polychlorinated monomers into the polyester film and using bisalkyl dimethylammonium salt for interfacial polymerization, the shortcomings in the existing polyester films in molecular weight regulation and separation capabilities of small molecule substances are solved, and more efficient separation performance and structural uniformity are achieved.

CN119565407APending Publication Date: 2025-03-07苏州仿生材料科学与工程中心
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411867584.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-20
Filing Date
2024-12-18
Publication Date
2025-03-07

Smart Images

  • Figure CN119565407A_ABST
    Figure CN119565407A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite films, in particular to a polyester composite film and a preparation method and application thereof. The polyester composite membrane comprises a support membrane and a polyester separation layer, wherein the polyester separation layer comprises a polybasic hydroxyl monomer and a polybasic acyl chloride monomer. The polyester composite membrane provided by the invention can accurately regulate and control the effective cut-off molecular weight, can overcome the technical limitation that the existing polyester membrane is difficult to effectively separate small molecules especially in the aspect of separation of small molecular substances, and improves the separation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Chinese patent application CN202311764206.7, filed on December 20, 2023, entitled “Polyester composite film, preparation method and application thereof”, the entire contents of which are incorporated herein by reference. Background Art

[0002] Existing polyester membranes have limited ability to regulate effective molecular weight cutoff, especially in the separation of small molecules, and often fail to achieve ideal results, limiting their applicability in diverse applications. In addition, although the structural uniformity of polyester membranes is still not ideal, the pore size distribution of the membrane is relatively wide, which in turn affects the precise separation performance and separation stability of the membrane. Summary of the invention

[0003] The main purpose of the present invention is to provide a polyester composite film to overcome the deficiencies of the prior art.

[0004] Another object of the present invention is to provide a method for preparing a polyester composite film to overcome the deficiencies of the prior art.

[0005] Another object of the present invention is to provide an application of the polyester composite film.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] According to a first aspect of the present invention, there is provided a polyester composite membrane, comprising a support membrane and a polyester separation layer, wherein the polyester separation layer comprises a polyhydroxy monomer and a polyacyl chloride monomer.

[0008] Optionally, the interception rate of the polyester composite membrane for sodium chloride solution is greater than or equal to 90%.

[0009] Optionally, the effective molecular weight cutoff of the polyester composite membrane is any value in the range of 100Da-2000Da.

[0010] Optionally, the effective molecular weight cutoff of the polyester composite membrane is any value in the range of 50Da-300Da.

[0011] Optionally, the thickness of the polyester composite film is any value in the range of 10 nm to 300 nm.

[0012] Optionally, under electron microscope observation, the surface of the polyester composite film is a smooth surface.

[0013] Optionally, the polyester composite film further comprises an oil-soluble surfactant, and the oil-soluble surfactant is a dialkyl dimethyl ammonium salt.

[0014] Optionally, the dialkyldimethylammonium salt includes any one of dioctadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide, and didecyldimethylammonium chloride, or a combination of two or more thereof.

[0015] Optionally, the polyester composite film further includes a water-soluble surfactant.

[0016] Optionally, the water-soluble surfactant includes any one or a combination of two or more of an amine salt type surfactant, a quaternary ammonium salt type surfactant, a heterocyclic type surfactant, an anionic sulfonate type surfactant and a carboxybetaine type surfactant.

[0017] Optionally, the amine salt type surfactant includes any one of n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, and n-octadecylamine, or a combination of two or more thereof.

[0018] Optionally, the quaternary ammonium salt surfactant includes any one of octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, behenyltrimethylammonium chloride, and behenyltrimethylammonium bromide, or a combination of two or more thereof.

[0019] Optionally, the anionic sulfonate surfactant includes any one of sodium dodecyl sulfonate, sodium hexadecyl sulfonate, sodium behenyl sulfonate, and sodium octane sulfonate, or a combination of two or more thereof.

[0020] Optionally, the carboxy betaine surfactant includes any one of decyl betaine, cocamidopropyl betaine, lauryl amide propyl betaine, and carboxy betaine, or a combination of two or more thereof.

[0021] Optionally, the polyhydroxy monomer includes any one or a combination of two or more of tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanidin, proanthocyanidin, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallate, catechin, epicatechin, epicatechin gallate, quercetin, hesperidin, naringenin, daidzein, curcumin, anthocyanin, cyclodextrin, sodium alginate, resveratrol, bisphenol A, catechol, hydroquinone, and phloroglucinol.

[0022] Optionally, the polyacyl chloride monomer includes any one or a combination of two or more of trimesoyl chloride, isophthaloyl chloride, phthaloyl chloride, adipoyl chloride and terephthaloyl chloride.

[0023] Optionally, the oil phase solution further comprises an organic solvent.

[0024] Optionally, the organic solvent includes any one of n-hexane, cyclohexane, and benzene, or a combination of two or more thereof.

[0025] Optionally, the polyester composite membrane includes a polyester composite reverse osmosis membrane or a polyester composite nanofiltration membrane.

[0026] Optionally, the support membrane is an ultrafiltration membrane.

[0027] Optionally, the ultrafiltration membrane includes any one of polyethersulfone ultrafiltration membrane, PVDF ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polysulfone ultrafiltration membrane, and nanocomposite ultrafiltration membrane, or a combination of two or more thereof.

[0028] Optionally, the effective pore size of the ultrafiltration membrane is 5-100 nm.

[0029] According to a second aspect of the present invention, an oil-soluble surfactant is provided for use in the preparation of a polyester separation membrane in a polyester composite membrane, wherein the oil-soluble surfactant is a dialkyl dimethyl ammonium salt.

[0030] Optionally, the dialkyldimethylammonium salt includes any one of dioctadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide, and didecyldimethylammonium chloride, or a combination of two or more thereof.

[0031] According to the third aspect of the present invention, a water-soluble surfactant is provided for use in the preparation of polyester separation membranes in polyester composite membranes, wherein the water-soluble surfactant comprises any one or a combination of two or more of an amine salt type surfactant, a quaternary ammonium salt type surfactant, a heterocyclic surfactant, an anionic sulfonate type surfactant and a carboxybetaine type surfactant.

[0032] Optionally, the amine salt type surfactant includes any one of n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, and n-octadecylamine, or a combination of two or more thereof.

[0033] Optionally, the quaternary ammonium salt surfactant includes any one of octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, behenyltrimethylammonium chloride, and behenyltrimethylammonium bromide, or a combination of two or more thereof.

[0034] Optionally, the anionic sulfonate surfactant includes any one of sodium dodecyl sulfonate, sodium hexadecyl sulfonate, sodium behenyl sulfonate, and sodium octane sulfonate, or a combination of two or more thereof.

[0035] Optionally, the carboxy betaine surfactant includes any one of decyl betaine, cocamidopropyl betaine, lauryl amide propyl betaine, and carboxy betaine, or a combination of two or more thereof.

[0036] According to a fourth aspect of the present invention, there is provided a polyhydroxy monomer for use in the preparation of a polyester separation membrane in a polyester composite membrane.

[0037] Optionally, the polyhydroxy monomer is any one or a combination of two or more of flavonol compounds, flavonoid compounds, catechol compounds, polysaccharide compounds and anthocyanin compounds.

[0038] Optionally, the chemical structural formula of the flavonol compound is:

[0039]

[0040] The chemical structural formula of the flavonoid compound is:

[0041]

[0042] The chemical structural formula of the catechol compound is:

[0043]

[0044] The chemical structural formula of the anthocyanin compound is:

[0045]

[0046] Wherein, R1 and R2 are both OH, and R3 is an arbitrary substituent.

[0047] Optionally, the polyphenol hydroxyl monomer specifically includes any one or a combination of two or more of tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanidin, proanthocyanidin, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallate, catechin, epicatechin, epicatechin gallate, quercetin, hesperidin, naringenin, daidzein, curcumin, anthocyanin, cyclodextrin, sodium alginate, and resveratrol.

[0048] Optionally, the aqueous solution for preparing the polyester separation membrane includes the polyhydroxy monomer and the water-soluble surfactant as described above.

[0049] According to a fifth aspect of the present invention, there is provided a method for preparing a polyester composite film, comprising the following steps:

[0050] Providing an aqueous phase solution containing a polyhydroxyl monomer and an oil phase solution containing a polyacyl chloride monomer;

[0051] With the porous support membrane as the support interface, the polyhydroxy monomers in the aqueous solution and the polyacyl chloride monomers in the oil solution undergo interfacial polymerization at the water / oil interface, thereby preparing a polyester composite membrane.

[0052] Optionally, the concentration of the polyhydroxy monomer in the aqueous solution is any value in the range of 0.5 g / L-15 g / L.

[0053] Optionally, the concentration of the polyacyl chloride monomer in the oil phase solution is any value in the range of 0.5 g / L-30 g / L.

[0054] Optionally, the oil phase solution further comprises an oil-soluble surfactant, and the concentration of the oil-soluble surfactant is any value in the range of 0.0001 g / L-100 g / L.

[0055] Optionally, the aqueous phase solution further comprises a water-soluble surfactant, and the concentration of the water-soluble surfactant is any value in the range of 0.0001 g / L-100 g / L.

[0056] Optionally, the method of using a porous support membrane as a support interface to allow polyhydroxy monomers in an aqueous solution and polyacyl chloride monomers in an oil phase solution to undergo interfacial polymerization at a water / oil interface to prepare a polyester composite membrane comprises the following steps:

[0057] Under the conditions of a temperature of 15-40° C. and a relative humidity of 20-80%, applying the aqueous phase solution to the surface of the support film, leaving it for 10-300 seconds, then applying the oil phase solution and leaving it for 10-1800 seconds;

[0058] The polyester composite film is prepared by annealing at 20-90°C for 5-30 minutes.

[0059] According to a sixth aspect of the present invention, there is provided an application of the aforementioned polyester composite membrane, which is applied in the fields of seawater desalination, water treatment, chemical liquid treatment, concentration, hemodialysis, drug separation, food processing or environmental protection.

[0060] The polyester composite membrane of the present invention can more accurately regulate the effective molecular weight cutoff, especially in the separation of small molecules, and can overcome the technical limitation of existing polyester membranes that are difficult to effectively separate small molecules, thereby improving the separation effect.

[0061] Furthermore, although in theory the long-chain alkyl structure of the dialkyl dimethyl ammonium salt may produce excessive interactions with other reaction components, resulting in interface instability or uneven polymerization, the embodiments of the present invention have successfully achieved uniformity of interfacial polymerization reaction through experimental verification. This is because the dialkyl dimethyl ammonium salt forms a dynamic equilibrium with other components in the water phase and the oil phase, avoiding unfavorable excessive interactions. This balancing action ensures the interfacial stability in the reaction system and overcomes the potential adverse effects expected in theory.

[0062] In the process of interfacial reaction, the addition of dialkyl dimethyl ammonium salt plays a key role. On the one hand, the quaternary ammonium group, as a Lewis acid catalyst, can form an acid-base ion pair with the hydroxyl functional group of the polyhydroxyl monomer, significantly reducing the interfacial reaction energy barrier between the polyhydroxyl monomer and the polyacyl chloride monomer, and promoting the reaction; on the other hand, the orderly assembly of dialkyl dimethyl ammonium salt at the reaction interface effectively promotes the aggregation of monomers at the interface. The lipophilicity of the dialkyl functional group strengthens the orderly arrangement of the surfactant at the interface, forming a more stable and continuous interface, thereby significantly increasing the accumulation of monomers at the interface and the monomer concentration in the reaction area, further accelerating the reaction rate.

[0063] In addition, dialkyl dimethyl ammonium salts also exhibit dual effects: first, they effectively stabilize the interface between the aqueous phase and the oil phase, preventing problems such as local excessive concentration or uneven interface during the interfacial polymerization reaction, and ensuring the structural uniformity of the membrane; second, the quaternary ammonium group of the dialkyl dimethyl ammonium salt carries a positive charge. This unique charge effect can electrostatically interact with the polyhydroxyl monomers or reaction intermediates in the aqueous phase, thereby accelerating the reaction rate. The electrostatic interaction between the quaternary ammonium group and the reactants reduces the reaction energy barrier and activates the polymerization reaction at the interface. This effect not only improves the uniformity of the pore structure of the membrane, but also optimizes the overall performance of the membrane.

[0064] In addition, the hydrophobic chains in the dialkyldimethylammonium salt form a microenvironment in the oil phase. This microenvironment has a dual role: on the one hand, it further improves the stability of the interface between the oil phase and the water phase, preventing interface rupture or uneven reaction; on the other hand, the presence of the hydrophobic chain regulates the size of the membrane pore size, making it more uniform and controllable, avoiding the situation where the pore size is too large or unevenly distributed. Compared with conventional surfactants (such as hexadecyldimethylammonium chloride with a single hydrophobic chain structure), this shows a stronger pore size regulation ability and has significant advantages in regulating membrane density.

[0065] Therefore, in the embodiment of the present invention, the double hydrophobic chains of the dialkyl dimethyl ammonium salt promote a more orderly molecular arrangement at the interface, thereby enhancing the compactness of the membrane structure. This dual effect not only stabilizes the interface, but also provides a new idea for the precise regulation of the membrane pore size, breaking through the traditional theory's expectation of the negative impact of long-chain surfactants in interfacial polymerization reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 A transmission electron microscope cross-sectional view of a polyester composite film according to an embodiment of the present invention is shown;

[0067] Figure 2 The scanning electron microscope image of the polyester composite film in the prior art is shown;

[0068] Figure 3 A scanning electron microscope image of a polyester composite film according to an embodiment of the present invention is shown;

[0069] Figure 4 A schematic flow chart showing a method for preparing a polyester composite film according to an embodiment of the present invention;

[0070] Figure 5 The molecular weight cut-off diagram of the polyester film composite membrane of multiple embodiments of the present invention is shown;

[0071] Figure 6 The pore size distribution diagram of the polyester film composite membrane according to multiple embodiments of the present invention is shown;

[0072] Figure 7 The anti-pollution performance diagram of the polyester film composite membrane in Example 13 of the present invention is shown;

[0073] Figure 8 A graph showing the antifouling performance of commercial membrane BW30 in Example 16 is shown. DETAILED DESCRIPTION

[0074] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in conjunction with the accompanying drawings. It is to be understood that the specific embodiments described herein are only used to explain the present application, rather than to limit the present application. It should also be noted that, for ease of description, only some structures related to the present application are shown in the accompanying drawings, rather than all structures. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0075] The terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device comprising a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.

[0076] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0077] Figure 1 FIG. 2 shows a transmission electron microscope cross-sectional view of a polyester composite film according to an embodiment of the present invention. Figure 1 As shown, the polyester composite membrane comprises a support membrane and a polyester separation layer. The polyester separation layer comprises a polyhydroxyl monomer and a polyacyl chloride monomer.

[0078] The polyester composite membrane of the embodiment of the present invention can more accurately control the effective molecular weight cutoff, especially in the separation of small molecules, and can overcome the technical limitation of the existing polyester membrane that it is difficult to effectively separate small molecules, thereby improving the separation effect.

[0079] In some embodiments, the polyester composite membrane has a retention rate of greater than or equal to 90% for sodium chloride solution, for example, 90%, 92%, 94%, 95%, 97%, 98%, 99% or 99.5%, or any value greater than or equal to 90%. The high retention rate reflects that the pore size distribution of the membrane is uniform and the structure is more compact, thereby improving the stability of the separation performance and reducing the performance fluctuation caused by the uneven membrane structure during operation.

[0080] In some embodiments, the effective molecular weight cutoff of the polyester composite membrane is any value in the range of 100-2000Da. In some embodiments, the effective molecular weight cutoff of the polyester composite membrane is any value in the range of 50Da-300Da, for example, it can be 50Da, 130Da, 180Da, 240Da or 300Da. In some embodiments, the effective molecular weight cutoff of the polyester composite membrane is 100-200Da, for example, it can be 100Da, 150Da or 200Da. In other embodiments, the effective molecular weight cutoff of the polyester composite membrane is 300-500Da, for example, it can be 300Da, 350Da, 400Da, 450Da or 500Da. In other embodiments, the effective molecular weight cutoff of the polyester composite membrane can also be 500Da-1000Da or 1000Da-2000Da.

[0081] According to the scheme of the embodiment of the present invention, the adjustable range of the effective molecular weight cut-off can be from small molecules (such as 50Da) to large molecules (such as 2000Da), so that the membrane can adapt to different separation requirements. For example, small molecule interception is suitable for fields such as medicine and food that require high-precision separation, while large molecule interception can be used for applications such as water treatment and chemical industry that require lower separation accuracy. By controlling the range of effective molecular weight cut-off, users can choose suitable membrane materials according to specific application requirements. This flexibility is particularly critical in complex separation processes, and can achieve separation of different substances without changing equipment. Customizing different molecular weight cut-offs according to application requirements can achieve higher interception rates in the separation of substances of different concentrations and molecular sizes, thereby improving process efficiency and reducing energy consumption and costs.

[0082] In certain embodiments, the thickness of the polyester composite membrane is any value in the range of 10nm-300nm, for example, it can be 10nm, 20nm, 30nm, 50nm, 100nm, 150nm, 200nm, 250nm or 300nm, or any other value in the range of 10-300nm. By adjusting the thickness of the membrane, separation efficiency and interception capacity can be affected. Thinner membranes such as 10nm-100nm can provide lower mass transfer resistance, which helps to improve separation rate, while thicker membranes such as 300nm provide stronger mechanical strength and durability, which are suitable for processes that require longer operation. Membranes with a thickness in the range of 10nm to 300nm can take into account higher separation performance and mechanical strength. In practical applications, the selection of membrane thickness not only affects separation accuracy, but also relates to the physical stability and durability of the membrane, avoiding damage and performance degradation caused by too thin membranes. By providing a thickness range of 10nm-300nm, users can choose according to different separation requirements and operating conditions. For example, in the separation operation that requires rapid processing in the pharmaceutical and food industries, the rapid separation characteristics of thin films are more suitable, while in applications that require strong durability or higher separation accuracy, thicker membranes perform better. Therefore, the thickness range of 10-300nm is selected to find a balance between the membrane's permeation rate, separation accuracy, mechanical strength and stability to meet the needs of different application scenarios.

[0083] In some embodiments, under electron microscope observation, the surface of the polyester composite film exhibits a smooth feature. It should be explained that the "smooth" can be understood as the surface of the film being smooth, and there is basically no significant leaf-like or cluster structure. Under high-resolution imaging of an electron microscope, large leaf or cluster structures appear as obvious convex or hill structures, such as Figure 2 It is also necessary to understand that "substantially absent" means that the proportion of significant leaf or cluster structures is extremely low, usually less than 10%, or even less than 5% or 2%. This definition indicates that the irregular morphology on the surface of the polyester composite film only occupies a very small part or does not exist, ensuring that the surface of the film is smooth and uniform as a whole. Figure 3 As shown, taking scanning electron microscopy (SEM) as an example, at a magnification of less than a few hundred nanometers, it can be clearly observed that the surface of the polyester composite membrane of the embodiment of the present invention is overall flat, without large-scale protrusions or irregular deformations, which indicates that the membrane structure is uniform, which is conducive to its performance stability during the separation process.

[0084] In order to improve the structural uniformity of polyester composite membranes and the separation ability of small molecules, the inventors have tried a variety of methods. For example, by optimizing the reaction conditions, including regulating the types and ratios of polyhydroxyl monomers and polyacyl chloride monomers in the oil phase and water phase components, adjusting the temperature and time of the interfacial polymerization reaction, optimizing the post-treatment technology, etc., the properties of the two-phase interface, the structure and separation performance of the polyester membrane are adjusted. In addition, the inventors also tried to introduce methods based on intermediate layers and porous nanomaterial composites between the support membrane and the polyester separation membrane to improve the pore structure and separation effect of the membrane. Although these methods have improved the performance of the membrane to a certain extent, it is still difficult to achieve precise control of the monomer aggregation morphology and the polymerization process during the interfacial polymerization reaction. Therefore, when constructing nanofiltration membranes with uniform and dense pore structures, especially reverse osmosis membranes, there are still technical bottlenecks that are difficult to break through. Although post-treatment processes such as heat treatment and secondary cross-linking can improve the density and separation accuracy of polyester composite membranes to a certain extent, these processes have high energy consumption and complex steps. Therefore, while improving the performance of polyester composite membranes, the aforementioned methods are difficult to balance the relationship between process complexity, energy consumption and overall performance.

[0085] Adding surfactants is widely considered to be a method that can regulate interfacial properties. The inventors have tried to add a variety of surfactants to the system, such as alkylbenzene sulfonates and phosphate surfactants. These surfactants can regulate the oil-water interface characteristics, monomer diffusion and polymerization behavior in interfacial polymerization to a certain extent. However, although these surfactants have some effect, they are not effective in improving the structural uniformity of polyester composite membranes and the separation ability of small molecules. Considering the particularity of the oil-water interface during interfacial polymerization and the interaction between surfactants and monomers, the inventors tried to add dihexadecyl dimethyl ammonium chloride to the interfacial polymerization system. On the one hand, this surfactant uses the ammonium chloride group as a Lewis acid to interact with the hydroxyl monomers in the water phase, so that its hydrophilic end can effectively anchor the water phase monomers and promote the orderly aggregation of monomers along the mediation of the surfactant. On the other hand, its hexadecyl long chain with good lipophilicity can extend well to the oil phase, forming orderly aggregation at the oil-water interface, further strengthening the assembly and aggregation effect of the surfactant in the oil phase.

[0086] Through this strategy, the inventors found that dihexadecyl dimethyl ammonium chloride significantly improved the structural uniformity of polyester composite membranes and the separation performance of small molecules, and had little effect on other membrane properties, overcoming the limitations expected in theory and successfully breaking through technical prejudice. In addition, the inventors also conducted experimental verification on other oil-soluble surfactants. The results showed that in addition to dihexadecyl dimethyl ammonium chloride, other dialkyl dimethyl ammonium salt oil-soluble surfactants also showed the effect of significantly improving the structural uniformity of polyester composite membranes and the ability to separate small molecules.

[0087] Based on this, an embodiment of the present invention also provides a further solution, wherein the polyester composite film further comprises an oil-soluble surfactant, and the oil-soluble surfactant is a dialkyl dimethyl ammonium salt.

[0088] Although in theory the long-chain alkyl structure of the dialkyl dimethyl ammonium salt may produce excessive interactions with other reaction components, resulting in interface instability or uneven polymerization, the present invention successfully achieved uniformity of interfacial polymerization reaction through experimental verification. This is because the dialkyl dimethyl ammonium salt forms a dynamic equilibrium with other components in the water phase and the oil phase, avoiding unfavorable excessive interactions. This balancing action ensures the interfacial stability in the reaction system and overcomes the potential adverse effects expected in theory.

[0089] In the process of interfacial reaction, the addition of dialkyl dimethyl ammonium salt plays a key role. On the one hand, the quaternary ammonium group, as a Lewis acid catalyst, can form an acid-base ion pair with the hydroxyl functional group of the polyhydroxyl monomer, significantly reducing the interfacial reaction energy barrier between the polyhydroxyl monomer and the polyacyl chloride monomer, and promoting the reaction; on the other hand, the orderly assembly of dialkyl dimethyl ammonium salt at the reaction interface effectively promotes the aggregation of monomers at the interface. The lipophilicity of the dialkyl functional group strengthens the orderly arrangement of the surfactant at the interface, forming a more stable and continuous interface, thereby significantly increasing the accumulation of monomers at the interface and the monomer concentration in the reaction area, further accelerating the reaction rate.

[0090] In addition, dialkyl dimethyl ammonium salts also exhibit dual effects: first, they effectively stabilize the interface between the aqueous phase and the oil phase, preventing problems such as local excessive concentration or uneven interface during the interfacial polymerization reaction, and ensuring the structural uniformity of the membrane; second, the quaternary ammonium group of the dialkyl dimethyl ammonium salt carries a positive charge. This unique charge effect can electrostatically interact with the polyhydroxyl monomers or reaction intermediates in the aqueous phase, thereby accelerating the reaction rate. The electrostatic interaction between the quaternary ammonium group and the reactants reduces the reaction energy barrier and activates the polymerization reaction at the interface. This effect not only improves the uniformity of the pore structure of the membrane, but also optimizes the overall performance of the membrane.

[0091] In addition, the hydrophobic chains in the dialkyldimethylammonium salt form a microenvironment in the oil phase. This microenvironment has a dual role: on the one hand, it further improves the stability of the interface between the oil phase and the water phase, preventing interface rupture or uneven reaction; on the other hand, the presence of the hydrophobic chain regulates the size of the membrane pore size, making it more uniform and controllable, avoiding the situation where the pore size is too large or unevenly distributed. Compared with conventional surfactants (such as hexadecyldimethylammonium chloride with a single hydrophobic chain structure), this shows a stronger pore size regulation ability and has significant advantages in regulating membrane density.

[0092] Therefore, in the embodiment of the present invention, the double hydrophobic chains of the dialkyl dimethyl ammonium salt promote a more orderly molecular arrangement at the interface, thereby enhancing the compactness of the membrane structure. This dual effect not only stabilizes the interface, but also provides a new idea for the precise regulation of the membrane pore size, breaking through the traditional theory's expectation of the negative impact of long-chain surfactants in interfacial polymerization reactions.

[0093] In some embodiments, the dialkyldimethylammonium salt includes any one of dioctadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide, and didecyldimethylammonium chloride, or a combination of two or more thereof.

[0094] In order to further improve the structural uniformity of the polyester composite membrane and the separation ability of small molecules, the aqueous phase solution also includes a water-soluble surfactant. The water-soluble surfactant includes any one or a combination of two or more of an amine salt surfactant, a quaternary ammonium salt surfactant, a heterocyclic surfactant, an anionic sulfonate surfactant, and a carboxybetaine surfactant.

[0095] The introduction of water-soluble surfactants plays a key synergistic role in the preparation of polyester films, which is specifically reflected in the following aspects: First, interfacial stability, that is, by reducing the interfacial tension between the water phase and the oil phase, the stability between the two phases is enhanced. This stability helps to prevent local concentration fluctuations and unevenness during the interfacial polymerization reaction and ensure the structural uniformity of the film. Second, the synergistic effect with oil-soluble surfactants, that is, dialkyl dimethyl ammonium salts play a role in interfacial stability and polymerization rate regulation in the oil phase, while water-soluble surfactants form a complementary relationship with them and act together on the reaction interface. Water-soluble surfactants further enhance the interaction between the oil phase and the water phase by providing additional interfacial activity, thereby improving the uniformity of the polymerization reaction. Third, the polymerization reaction rate regulation, that is, the charge characteristics of water-soluble surfactants can form electrostatic interactions with polyhydroxy monomers in the water phase, promote their diffusion to the oil-water interface and reaction with reactants in the oil phase. This synergistic effect improves the rate and efficiency of the polymerization reaction. Fourth, the pore structure is optimized, that is, through the combination of appropriate water-soluble surfactants, the pore size of the polyester membrane can be effectively regulated. This regulation, together with the oil-soluble surfactant, helps to construct a narrowly distributed pore structure, thereby improving the separation selectivity of the membrane for small molecules. Fifth, the anti-pollution ability of the membrane is improved. The water-soluble surfactant and the oil-soluble surfactant work synergistically to construct a polyester film with a uniform pore structure and a smooth surface structure. The smooth polyester surface film can reduce the adsorption and deposition of pollutants on the surface during the separation process, and enhance its anti-pollution performance and separation stability in long-term use. Therefore, the direct interaction between the water-soluble surfactant and other components in the water phase and the oil phase, especially the oil-soluble surfactant, greatly optimizes the preparation process of the polyester composite membrane and improves the structural uniformity and separation performance of the membrane.

[0096] In some embodiments, amine salt type surfactants include any one or a combination of two or more of n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine, and n-octadecylamine. Quaternary ammonium salt type surfactants include any one or a combination of two or more of octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, behenyltrimethylammonium chloride, and behenyltrimethylammonium bromide. Anionic sulfonate surfactants include any one or a combination of two or more of sodium dodecylsulfonate, sodium hexadecylsulfonate, sodium behenylsulfonate, and sodium octylsulfonate. Carboxy betaine surfactants include any one or a combination of two or more of decyl betaine, cocamidopropyl betaine, laurylamidopropyl betaine, and carboxy betaine.

[0097] In some embodiments, the polyhydroxy monomer includes any one or a combination of two or more of tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanidin, proanthocyanidin, bisphenol A, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallate, catechin, epicatechin, epicatechin gallate, quercetin, hesperidin, naringenin, daidzein, curcumin, and anthocyanin.

[0098] The polyacyl chloride monomer includes any one or a combination of two or more of trimesoyl chloride, isophthaloyl chloride, phthaloyl chloride, adipoyl chloride and terephthaloyl chloride. The oil phase solution also includes an organic solvent. The organic solvent includes any one or a combination of two or more of n-hexane, cyclohexane and benzene.

[0099] In one embodiment, the polyester composite membrane includes a polyester composite reverse osmosis membrane or a polyester composite nanofiltration membrane. The porous support membrane is an ultrafiltration membrane, and the effective pore size of the ultrafiltration membrane is 5nm-100nm, for example, it can be 5nm, 10nm, 15nm, 20nm, 30nm, 50nm, 70nm, 80nm, 90nm or 100nm, or it can be other values ​​in 5nm-100nm. The ultrafiltration membrane includes any one of polyethersulfone ultrafiltration membrane, PVDF ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polysulfone ultrafiltration membrane, and nanocomposite ultrafiltration membrane, or a combination of two or more. The polyester composite membrane has a flux recovery rate of greater than 97.04% for bovine serum albumin with a concentration of 100ppm. The retention rate of the polyester composite membrane for a sodium chloride solution with a concentration of 2000ppm is less than or equal to 99.6%, and the salt flux is greater than 1.2Lm -2 h - 1 bar -1 .

[0100] According to another aspect of an embodiment of the present invention, an oil-soluble surfactant is provided for use in the preparation of a polyester separation membrane in a polyester composite membrane, wherein the oil-soluble surfactant is a dialkyl dimethyl ammonium salt. In one embodiment, the polyester composite membrane is the polyester composite membrane described above, and other features related to the oil-soluble surfactant are consistent with the above description and are not repeated here.

[0101] According to another aspect of an embodiment of the present invention, a water-soluble surfactant is provided for use in the preparation of a polyester separation membrane in a polyester composite membrane. The water-soluble surfactant includes any one or a combination of two or more of an amine salt surfactant, a quaternary ammonium salt surfactant, a heterocyclic surfactant, an anionic sulfonate surfactant, and a carboxybetaine surfactant. In one embodiment, the polyester composite membrane is the polyester composite membrane described above, and other features related to the water-soluble surfactant are consistent with the above description and are not repeated here.

[0102] Water-soluble surfactants can regulate the properties of the oil-water interface and promote the uniformity of interfacial polymerization by reducing interfacial tension and adjusting the compatibility of the two phases. Different types of surfactants help adjust the diffusion rate of monomers at the interface through the action of their hydrophilic and lipophilic ends, thereby affecting the pore structure and thickness of the membrane. Water-soluble surfactants can effectively control the distribution and aggregation morphology of polymer chains at the interface. During the interfacial polymerization reaction, water-soluble surfactants form a stable molecular layer at the interface of the oil phase and the water phase through their amphiphilic structure, which plays a role in stabilizing the reaction environment, reducing the irregular distribution of monomers during polymerization, and avoiding excessive aggregation or uneven aggregation. The introduction of water-soluble surfactants can improve the retention capacity of polyester composite membranes for specific small molecules by regulating the pore structure of the membrane. Some surfactants can interact with specific monomers, regulate their diffusion and reaction rates, and thus affect the pore size of the membrane. This adjustment helps to optimize the selectivity of the membrane, enabling it to better retain small molecules, especially small molecules with a molecular weight range of hundreds to thousands of Daltons. During the membrane preparation process, some irregular membrane pores or membrane layer defects may be generated due to the uneven interfacial polymerization reaction. Water-soluble surfactants can reduce the formation of irregular cluster structures or pores, reduce the deviation of membrane pore size distribution, and prevent significant membrane defects by stabilizing the interfacial reaction environment.

[0103] Moreover, by properly matching water-soluble surfactants and oil-soluble surfactants, stable molecular arrangement can be achieved at the interface, interfacial polymerization reaction conditions can be optimized, and the selectivity and performance stability of the membrane can be improved. The matching principle of water-soluble surfactants and oil-soluble surfactants in interfacial polymerization is based on their molecular structure characteristics and interaction characteristics, mainly considering the structure of hydrophilic head groups and hydrophobic segments, as well as the synergistic effect between the two and the aqueous phase monomer molecules at the interface. The following is a detailed description of the matching rules.

[0104] First, consider the chemical property matching of the head group. The head group (hydrophilic end) of water-soluble surfactants and oil-soluble surfactants should be matched with the chemical structure of the aqueous phase monomer based on their chemical structure and charge characteristics. For example, anionic sulfonate surfactants are more suitable for matching with amine aqueous phase monomers to balance the charge distribution and stabilize the interface.

[0105] Secondly, consider the matching of hydrophobic chain length. The length of the hydrophobic chain of water-soluble surfactants and oil-soluble surfactants should ensure that the range of activity of the hydrophobic chain in the oil phase solution does not affect the orderly arrangement of the surfactant molecules at the interface, ensuring the close stacking of the interface molecules.

[0106] Through the above rules and matching strategies, the combination of water-soluble and oil-soluble surfactants can be accurately selected to improve the stability and efficiency of the interfacial polymerization reaction and optimize the pore size distribution and selectivity of the membrane.

[0107] The aqueous phase monomers of polyester separation membranes in the prior art usually select amine monomers, which are widely used due to their high reactivity and excellent polymerization characteristics. However, although amine monomers have some advantages in membrane preparation, there are still some problems. For example, amine monomers are usually obtained by chemical synthesis, which may involve a large amount of chemical reagents and energy consumption, resulting in environmental pollution and waste of resources. For example, the environmental toxicity of amine monomers is relatively high. Inhalation and contact during the production process are harmful to the health of operators to a certain extent. The ammonia nitrogen content in the wastewater generated during the membrane making process is high, which is not conducive to environmental protection. For example, although amine monomers are highly reactive, under certain conditions (such as high temperature or extreme pH values), side reactions may occur, thereby affecting the structure and performance of the membrane. For example, in many cases, membranes prepared using amine monomers may have a contradiction between selectivity and flux. For example, in some cases, membranes prepared using amine monomers perform poorly in terms of selectivity for specific small molecules, which limits their application in separation technology.

[0108] Based on this, the inventors of the present application propose an alternative solution, namely, selecting a natural extract. The natural extract is a polyhydroxy monomer, which is used in the preparation of a polyester separation membrane in a polyester composite membrane. The polyester composite membrane can be, for example, the polyester composite membrane described above, which will not be described in detail here.

[0109] However, natural extracts have significant limitations compared to traditional amine monomers. These limitations are reflected in the following aspects. First, natural extracts mainly contain polyphenols and hydroxyl-functionalized compounds, which have relatively low reactivity, especially in the interfacial polymerization process. In contrast, amine monomers are generally more reactive and can polymerize more effectively with other monomers. Second, in the interfacial polymerization reaction, the lower reactivity of natural extracts leads to insufficient reaction, making it difficult to form a uniform, dense selective membrane, thereby affecting the separation performance and salt rejection ability of the membrane. Third, natural polyhydroxy monomers have low reactivity and are prone to form irregular polyester networks in the polymerization reaction, which has a negative impact on the functionality of the membrane, especially in high-salt water treatment applications.

[0110] The embodiment of the present application breaks the above limitations, and the polyhydroxy monomer can be selected as a natural polyhydroxy monomer. The natural polyhydroxy monomer is a natural extract.

[0111] The natural polyhydroxy monomer and the polyacyl chloride monomer undergo interfacial polymerization to form a polyester film. The natural polyhydroxy monomer usually contains multiple hydroxyl groups, which can effectively react with the polyacyl chloride monomer to form a covalent bond. During the interfacial polymerization process, the polyhydroxyl groups can react with the acyl chloride at the interface of the water and oil phases to form a polyester film. This reaction has high selectivity and stability, which helps to form a uniform membrane structure. In addition, the natural polyhydroxy monomer has high reactivity and can polymerize with the polyacyl chloride in the oil phase under a mild environment, thereby reducing the adverse effects of harsh environments on the film-forming process and membrane properties. The introduction of natural polyhydroxy monomers can significantly improve the uniformity of the membrane. During the polymerization process, the hydrophilic polyhydroxyl group can promote aggregation at the monomer interface to form a uniform polymer network. In addition, the structural characteristics of natural polyhydroxy compounds help to regulate the pore size and distribution of the membrane and optimize the performance of the membrane in the separation of small molecules.

[0112] Moreover, the differences in solubility and polarity between the natural polyhydroxyl monomer and the polyacyl chloride monomer enable them to dissolve in water and oil phases respectively, and form a film with an excellent cross-linked network structure in the interfacial polymerization reaction, thereby forming a membrane structure with good mechanical strength, thereby improving the mechanical strength of the membrane. The polyhydroxyl group can help improve the anti-fouling ability of the membrane. The molecular structure and functional group distribution of the two can form a complex cross-linked network during the polymerization process, optimize the pore structure of the membrane, and thus improve the selectivity and flux of the membrane. This structural matching helps to achieve efficient and precise performance in the separation process.

[0113] In order to further improve the performance of the polyester composite film, in some embodiments, the polyhydroxy monomer is any one or a combination of two or more of flavonol compounds, flavonoid compounds, catechol compounds, polysaccharide compounds and anthocyanin compounds.

[0114] The chemical structural formula of the flavonol compound is:

[0115]

[0116] The chemical structure of flavonoids is:

[0117]

[0118] The chemical structure of catechol compounds is:

[0119]

[0120] The chemical structure of anthocyanin compounds is:

[0121]

[0122] Wherein, R1 and R2 are both OH, and R3 is an arbitrary substituent.

[0123] In this embodiment, in the preparation process of the polyester composite film, in addition to the polyhydroxy monomer and the polyacyl chloride monomer, a water-soluble surfactant, an oil-soluble surfactant and an organic solvent are also included. The specific schemes of the water-soluble surfactant, the oil-soluble surfactant and the organic solvent are as described above and will not be repeated here. Other technical schemes of the polyhydroxy monomer and the polyacyl chloride monomer are also consistent with the above description and will not be repeated here.

[0124] It is understandable that although the polyhydroxy monomers described in the embodiments of the present application are natural monomers, artificially synthesized monomers can also achieve the same effect using the solutions of the embodiments of the present application. Therefore, the polyhydroxy monomers are not limited to natural monomers.

[0125] According to another aspect of the embodiments of the present invention, a method for preparing the aforementioned polyester composite film is provided. Figure 4 FIG. 1 is a schematic flow chart showing a method for preparing a polyester composite film according to an embodiment of the present invention. Figure 4 As shown, the preparation method comprises:

[0126] Step S100, providing an aqueous solution containing a polyhydroxyl monomer and an oil solution containing a polyacyl chloride monomer and an oil-soluble surfactant;

[0127] Step S200, using the porous support membrane as the support interface, allowing the polyhydroxy monomers in the aqueous solution and the polyacyl chloride monomers in the oil solution to undergo interfacial polymerization at the water / oil interface, thereby forming a polyester composite membrane to obtain a polyester composite membrane.

[0128] In step S100, the concentration of the polyhydric hydroxyl monomer in the aqueous solution is 0.5-15 g / L, for example, 5 g / L, 10 g / L, 12 g / L or 15 g / L, or any other value in the range of 0.5-15 g / L. The concentration of the polyhydric acyl chloride monomer in the oil solution is 0.5-30 g / L, for example, 0.5 g / L, 1.5 g / L, 3 g / L, 3.5 g / L, 5 g / L, 10 g / L, 20 g / L, 25 g / L or 30 g / L, or any other value in the range of 0.5-30 g / L. The concentration of the oil-soluble surfactant in the oil phase solution is 0.0001-100 g / L, for example, it can be 0.0001 g / L, 0.001 g / L, 0.01 g / L, 0.05 g / L, 1 g / L, 10 g / L, 50 g / L or 100 g / L, or any value between 0.0001 and 100 g / L.

[0129] If the monomer concentration is too low, the interfacial polymerization reaction rate will be too slow, and a longer reaction time will be required to achieve the desired degree of polymerization, thereby reducing production efficiency. On the contrary, if the monomer concentration is too high, although the reaction rate will be accelerated, the excessively high concentration may cause the reaction to be too violent and difficult to control, or even cause side reactions, affecting the performance of the membrane. If the surfactant concentration is too low, it will not form enough interfacial film to stabilize the interface, resulting in problems such as local excessive concentration or uneven interface during the polymerization reaction. On the contrary, if the surfactant concentration is too high, an overly thick interfacial film will be formed, hindering the effective contact and reaction of the monomer at the interface, thereby affecting the polymerization reaction. In addition, surfactants play an important role in regulating the pore size of the membrane. If the concentration is inappropriate, the distribution and size of the membrane pore size cannot be effectively regulated, resulting in decreased membrane performance. For example, if the pore size is too large, the interception effect will be reduced, while if the pore size is too small, the permeation resistance will increase.

[0130] The step S200 includes the following steps: applying the aqueous solution to the surface of the support membrane at a temperature of 15-40°C and a relative humidity of 20-80%, and then applying the oil phase solution and keeping it still for 10-1800 seconds; annealing for 5-30 minutes at 20-90°C to obtain a polyester composite membrane. Thus, a series of polyester thin film composite reverse osmosis / nanofiltration membranes with different molecular weight cutoffs are obtained, and finally the membranes are dried and stored or stored in deionized water.

[0131] Applying the solution in the temperature range of 15-40°C is conducive to maintaining the activity of the monomer and surfactant, while avoiding too fast or unstable reaction caused by too high temperature. A relative humidity of 20-80% helps to adjust the solvent evaporation rate at the interface, thereby affecting the thickness and density of the membrane. Appropriate humidity can reduce the rapid evaporation of the solvent at the interface and prevent defects on the membrane surface. After the aqueous phase solution is applied to the surface of the support membrane, it stays for 10-300s, giving the polyhydroxyl monomer time to fully infiltrate and adsorb on the surface of the support membrane, which helps the uniform distribution of the aqueous phase monomer on the surface of the support membrane, and then helps to form a more uniform interface layer. Apply the oil phase solution and let it stand for 10-1800s, so that the polyacyl chloride monomer and the polyhydroxyl monomer can fully contact and react at the interface to form a dense polyester layer. Long-term standing helps the reaction to proceed completely and reduce the unreacted monomer residue. Annealing treatment for 5-30min at 20-90°C can further promote the optimization and stabilization of the internal structure of the membrane. Annealing helps to eliminate stress in the membrane and improve the mechanical properties and thermal stability of the membrane. At the same time, annealing treatment can also promote the further reaction of the remaining reactants, making the membrane structure more dense and uniform, thereby improving the separation performance of the membrane.

[0132] In one embodiment, the aqueous phase solution also includes a water-soluble surfactant, and the concentration of the water-soluble surfactant is 0.0001-100g / L, for example, it can be 0.0001g / L, 0.001g / L, 0.01g / L, 0.05g / L, 1g / L, 10g / L, 50g / L or 100g / L, or any value in 0.0001-100g / L. Within this concentration range, the water-soluble surfactant can effectively reduce the interfacial tension between the aqueous phase and the oil phase and enhance the interfacial stability. This helps to prevent interfacial rupture or uneven reaction during the polymerization reaction, thereby ensuring the smooth progress of the reaction. The adsorption and arrangement of the water-soluble surfactant on the interface can accelerate the diffusion and reaction of the monomer at the interface, thereby optimizing the reaction rate. The appropriate reaction rate helps to form a polyester film with uniform structure and good performance. The water-soluble surfactant plays an important role in regulating and controlling the pore size during the film formation process. By adjusting the concentration of water-soluble surfactants, the distribution and size of membrane pore size can be indirectly affected, thereby preparing polyester thin film composite reverse osmosis / nanofiltration membranes with different molecular weight cutoffs. This is crucial to meet the needs of different applications. Appropriate water-soluble surfactant concentrations help form membrane structures with high flux and high selectivity. This can improve the separation efficiency of the membrane, allowing it to play a better role in water treatment, chemical separation and other fields. When the water-soluble surfactant is controlled within this concentration range, it can reduce the defects generated during the formation of the membrane, such as uneven pore size and wide size distribution caused by uneven polymerization, which helps to improve the overall quality and performance of the membrane.

[0133] According to a fourth aspect of the present invention, there is provided an application of a polyester composite membrane for use in seawater desalination, water treatment, chemical liquid treatment, concentration, hemodialysis, drug separation, food processing or environmental protection fields.

[0134] The technical scheme of the present invention is explained in more detail below in conjunction with several preferred embodiments and the accompanying drawings. The specific embodiments described below are only used to further illustrate and explain the present invention, and are not intended to limit the present invention. In the embodiments described below, the ultrafiltration membrane is exemplified by polyethersulfone membrane, the aqueous surfactant solution is exemplified by hexadecyltrimethylammonium chloride, the polyhydroxy monomer is exemplified by tannic acid and epigallocatechin gallate, the organic phase surfactant is exemplified by dioctadecyldimethylammonium chloride, the organic solvent is exemplified by n-hexane, and the polyacyl chloride monomer is exemplified by trimesoyl chloride. Some simple improvements based on the method of the present invention should all be within the scope of protection of the claims.

[0135] Example 1

[0136] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 15°C and a relative humidity of 60%. After 10 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 1800 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 20°C for 30 minutes, soak it in deionized water and store it.

[0137] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 24Lm -2 h -1 bar -1 The retention rate is 1.05%, and the effective molecular weight cutoff of the membrane is 1542Da.

[0138] Example 2

[0139] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 10 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 90°C for 30 minutes, soak it in deionized water and store it.

[0140] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15bar, and a flux of 25Lm -2 h -1 bar -1 The retention rate was 3.05%, and the effective molecular weight cutoff of the membrane was 1399Da.

[0141] Example 3

[0142] Tannic acid was dissolved in 1 / 160CMC hexadecyltrimethylammonium chloride solution to prepare 12g / L TA-CTAC (tannic acid-hexadecyltrimethylammonium chloride) aqueous solution, which was used to wet the surface of polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane was immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 30 minutes, soaked in deionized water and stored.

[0143] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 17Lm -2 h -1 bar -1 The retention rate was 19.08%, and the effective molecular weight cutoff of the membrane was 802Da.

[0144] Example 4

[0145] Dissolve tannic acid in 1 / 40CMC hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which is used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 30 minutes, soaked in deionized water, and stored.

[0146] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 6.6Lm -2 h -1 bar -1 The retention rate was 82.90%, and the effective molecular weight cutoff of the membrane was 390Da.

[0147] Example 5

[0148] Dissolve tannic acid in 1 / 10CMC hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which is used to soak the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 30 minutes, soaked in deionized water, and stored.

[0149] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 1.65Lm -2 h -1 bar -1 The retention rate was 91.01%, and the effective molecular weight cutoff of the membrane was 147Da.

[0150] Example 6

[0151] Dissolve tannic acid in 1CMC hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which is used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 30 minutes, soaked in deionized water and stored.

[0152] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 35bar, and the flux was 1.2Lm -2 h -1 bar -1 The retention rate is 99.60%, and the effective molecular weight cutoff of the membrane is 108Da.

[0153] Figure 5 The molecular weight cut-off diagram of the polyester thin film composite membrane according to various embodiments of the present invention is shown. Figure 5 The embodiments in Examples 2-6 are included, and other embodiments are also included, such as the effective molecular weight cutoff of the membrane when the surfactant concentration is 1 / 320 CMC. Figure 6 The pore size distribution diagram of the polyester thin film composite membrane according to multiple embodiments of the present invention is shown. Figure 6The embodiments of embodiments 2-6 are included, the membrane pore diameter of embodiment 2 is 0.99nm, the membrane pore diameter of embodiment 3 is 0.76nm, the membrane pore diameter of embodiment 4 is 0.54nm, the membrane pore diameter of embodiment 5 is 0.49nm, and the membrane pore diameter of embodiment 6 is 0.41nm.

[0154] Example 7

[0155] Dissolve tannic acid in a 0.5 g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 120 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2 g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0156] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 52Lm -2 h -1 bar -1 The retention rate is 0.05%, and the effective molecular weight cutoff of the membrane is 3142Da.

[0157] Example 8

[0158] Dissolve tannic acid in a 15g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 120 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0159] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 28Lm -2 h -1 bar -1 The retention rate was 8.05%, and the effective molecular weight cutoff of the membrane was 1125Da.

[0160] Example 9

[0161] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 120 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 0.5g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0162] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 48Lm -2 h -1 bar -1 The retention rate is 0.06%, and the effective molecular weight cutoff of the membrane is 3008Da.

[0163] Example 10

[0164] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 120 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 30g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0165] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15bar, and a flux of 15Lm -2 h -1 bar -1 The retention rate was 7.06%, and the effective molecular weight cutoff of the membrane was 1243Da.

[0166] Embodiment 11

[0167] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to wet the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 300 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0168] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15bar, and a flux of 20Lm -2 h -1 bar -1 The retention rate was 5.05%, and the effective molecular weight cutoff of the membrane was 1221Da.

[0169] Example 12

[0170] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to soak the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 10 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0171] The polyester film composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15 bar, and a flux of 40 Lm -2 h -1 bar -1 The retention rate was 2.05%, and the effective molecular weight cutoff of the membrane was 1301Da.

[0172] Example 13

[0173] Dissolve tannic acid in a 12g / L aqueous solution (without surfactant) and use it to wet the surface of a polyethersulfone ultrafiltration membrane at a temperature of 40°C and a relative humidity of 60%. After 300 seconds, absorb the solution on the membrane surface and then soak the membrane surface in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, soak the membrane in hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0174] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution, the test temperature was 25°C, the operating pressure was 15bar, and the flux was 18Lm -2 h -1 bar -1 The retention rate was 7.05%, and the effective molecular weight cutoff of the membrane was 1202Da.

[0175] Embodiment 14

[0176] Dissolve tannic acid in 0.0001g / L hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which is used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 80%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 30 minutes, soaked in deionized water, and stored.

[0177] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 35bar, and a flux of 1.5Lm -2 h -1 bar -1 The retention rate was 98.60%, and the effective molecular weight cutoff of the membrane was 312Da.

[0178] Embodiment 15

[0179] Dissolve tannic acid in 100g / L hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which is used to soak the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 20%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 5 minutes, soaked in deionized water, and stored.

[0180] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 35bar, and the flux was 8.8Lm -2 h -1 bar -1 The retention rate was 91.30%, and the effective molecular weight cutoff of the membrane was 198Da.

[0181] Example 16

[0182] The polyester film composite membrane prepared in Example 13 and the commercial membrane BW30 were tested for anti-fouling performance under the same conditions (15.5 bar, 100 ppm BSA, 25°C). Deionized water was used to press the membrane for 2 hours in advance, and the water flux was recorded; the deionized water was replaced with a pre-prepared BSA solution and filtered for 3.5 hours, and the flux of BSA was recorded. Then the pump was washed for 1 hour and deionized water was injected again to test the water flux. This was repeated twice, and the flux recovery rate was calculated.

[0183] After testing, such as Figure 7As shown, the flux recovery rate of the polyester film composite membrane prepared in Example 5 is 97.04%. Figure 8 As shown, the flux recovery rate of the commercial membrane BW30 is 38.47%.

[0184] Embodiment 17

[0185] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / dioctadecyl dimethyl ammonium chloride (1CMC) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0186] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15 bar, and a flux of 1.3 Lm -2 h -1 bar -1 The retention rate was 97.20% and the molecular weight cutoff of the membrane was 123Da.

[0187] Embodiment 18

[0188] Epigallocatechin gallate was dissolved in a 12 g / L aqueous solution (without surfactant) and used to wet the surface of a polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was blotted dry, and then the membrane surface was immersed in a 2 g / L trimesoyl chloride n-hexane solution. After 300 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 30 minutes, immersed in deionized water, and stored.

[0189] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar, and the flux was 18.62 Lm -2 h -1 bar -1 , the interception rate is 0.65%.

[0190] Embodiment 19

[0191] Epigallocatechin gallate was dissolved in 1CMC hexadecyltrimethylammonium chloride solution to prepare a 12g / L TA-CTAC aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 30 minutes, immersed in deionized water and stored.

[0192] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar, and the flux was 6.58 Lm -2 h -1 bar -1 The retention rate was 87.19%, and the effective molecular weight cutoff of the membrane was 238Da.

[0193] Embodiment 20

[0194] Dissolve tannic acid in 1CMC octadecyltrimethylammonium chloride solution to prepare 12g / L TA-OTAC aqueous solution, which is used to soak the surface of polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface is dried, and then the membrane surface is immersed in a 2g / L hexane solution of trimesoyl chloride. After 120 seconds of reaction, the membrane is immersed in hexane to wash away excess trimesoyl chloride. Finally, the membrane is heated at 60°C for 30 minutes, soaked in deionized water and stored.

[0195] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15bar, and the flux was 3.17Lm -2 h -1 bar -1 , the interception rate was 94.28%.

[0196] Embodiment 21

[0197] Dissolve tannic acid in 1CMC tetradecyltrimethylammonium chloride solution to prepare 12g / L TA-OTAC aqueous solution, which is used to soak the surface of polyethersulfone ultrafiltration membrane at 25°C and 60% relative humidity. After 120 seconds, absorb the solution on the membrane surface, and then soak the membrane surface in 2g / L trimesoyl chloride n-hexane solution. After 120 seconds of reaction, soak the membrane in n-hexane to wash away excess trimesoyl chloride. Finally, heat the membrane at 60°C for 30 minutes, soak it in deionized water and store it.

[0198] After testing, the polyester film composite membrane prepared in this embodiment was tested with a 2000ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15bar, and the flux was 0.39Lm -2 h -1 bar -1 , the interception rate is 92.66%.

[0199] Embodiment 22

[0200] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / dioctadecyl dimethyl ammonium chloride (0.0001g / L) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0201] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15 bar, and a flux of 1.3 Lm -2 h -1 bar -1 The retention rate was 97.20% and the molecular weight cutoff of the membrane was 123Da.

[0202] Embodiment 23

[0203] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / dioctadecyl dimethyl ammonium chloride (100g / L) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0204] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15 bar, and a flux of 1.8 Lm -2 h -1 bar -1 The retention rate was 90.20% and the molecular weight cutoff of the membrane was 223Da.

[0205] Embodiment 24

[0206] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / dioctadecyl dimethyl ammonium chloride (50g / L) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0207] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C, an operating pressure of 15 bar, and a flux of 1.3 Lm -2 h -1 bar -1 The retention rate was 87.20% and the molecular weight cutoff of the membrane was 345Da.

[0208] Comparative Example 1

[0209] The conditions of Reference Example 17 were followed, except that the oil-soluble surfactant was changed to sodium dodecylbenzenesulfonate.

[0210] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / sodium dodecylbenzene sulfonate (1CMC) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0211] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar, and the flux was 11.2 Lm -2 h -1 bar -1 The retention rate was 23.20% and the molecular weight cutoff of the membrane was 1230Da.

[0212] Comparative Example 2

[0213] The conditions of Reference Example 17 were followed, except that the oil-soluble surfactant was changed to dibutyl phosphate.

[0214] Tannic acid was dissolved in water to prepare a 12g / L TA aqueous solution, which was used to wet the surface of the polyethersulfone ultrafiltration membrane at a temperature of 25°C and a relative humidity of 60%. After 120 seconds, the solution on the membrane surface was dried, and then the membrane surface was immersed in a 2g / L trimesoyl chloride / dibutyl phosphate (1CMC) n-hexane solution. After 120 seconds of reaction, the membrane was immersed in n-hexane to wash away excess trimesoyl chloride. Finally, the membrane was heated at 60°C for 15 minutes, immersed in deionized water, and stored.

[0215] After testing, the polyester composite membrane prepared in this embodiment was tested with a 2000 ppm NaCl aqueous solution at a test temperature of 25°C and an operating pressure of 15 bar, and the flux was 10.2 Lm -2 h -1 bar -1 The retention rate is 33.20%, and the molecular weight cutoff of the membrane is 850Da.

[0216] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the methods of Examples 1 to 24, and similarly prepared a series of polyester film composite reverse osmosis / nanofiltration membranes with different effective molecular weight cutoffs.

[0217] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0218] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A polyester composite film, characterized in that: The invention comprises a supporting film and a polyester separation layer, wherein the polyester separation layer comprises a polyhydroxyl monomer and a polyacyl chloride monomer.

2. The polyester composite film according to claim 1, characterized in that: The interception rate of the polyester composite membrane to the sodium chloride solution is greater than or equal to 90%.

3. The polyester composite film according to claim 1, characterized in that: The effective molecular weight cutoff of the polyester composite membrane is any value in the range of 100Da-2000Da; Optionally, the effective molecular weight cutoff of the polyester composite membrane is any value in the range of 50Da-300Da.

4. The polyester composite film according to claim 1, characterized in that: The thickness of the polyester composite film is any value in the range of 10nm-300nm; Optionally, under electron microscope observation, the surface of the polyester composite film is a smooth surface.

5. The polyester composite film according to any one of claims 1 to 4, characterized in that: The polyester composite film further comprises an oil-soluble surfactant, and the oil-soluble surfactant is a dialkyl dimethyl ammonium salt; Optionally, the dialkyldimethylammonium salt includes any one of dioctadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide, and didecyldimethylammonium chloride, or a combination of two or more thereof; Optionally, the polyester composite film further comprises a water-soluble surfactant; Optionally, the water-soluble surfactant includes any one or a combination of two or more of an amine salt surfactant, a quaternary ammonium salt surfactant, a heterocyclic surfactant, an anionic sulfonate surfactant and a carboxybetaine surfactant; Optionally, the amine salt type surfactant includes any one or a combination of two or more of n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine and n-octadecylamine; Optionally, the quaternary ammonium salt surfactant includes any one of octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, behenyltrimethylammonium chloride, and behenyltrimethylammonium bromide, or a combination of two or more thereof; Optionally, the anionic sulfonate surfactant includes any one or a combination of two or more of sodium dodecyl sulfonate, sodium hexadecyl sulfonate, sodium behenyl sulfonate, and sodium octane sulfonate; Optionally, the carboxy betaine surfactant includes any one of decyl betaine, cocamidopropyl betaine, lauryl amide propyl betaine, and carboxy betaine, or a combination of two or more thereof.

6. The polyester composite film according to any one of claims 1 to 4, characterized in that: The polyhydroxy monomer includes any one or a combination of two or more of tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanidin, proanthocyanidin, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallate, catechin, epicatechin, epicatechin gallate, quercetin, hesperidin, naringenin, daidzein, curcumin, anthocyanin, cyclodextrin, sodium alginate, resveratrol, bisphenol A, catechol, hydroquinone, and phloroglucinol; Optionally, the polyacyl chloride monomer includes any one or a combination of two or more of trimesoyl chloride, isophthaloyl chloride, phthaloyl chloride, adipoyl chloride and terephthaloyl chloride; Optionally, the polyester composite membrane is formed by an interfacial polymerization reaction of an aqueous solution and an oil solution, and the oil solution further comprises an organic solvent; Optionally, the organic solvent includes any one or a combination of two or more of n-hexane, cyclohexane and benzene; Optionally, the polyester composite membrane includes a polyester composite reverse osmosis membrane or a polyester composite nanofiltration membrane; Optionally, the support membrane is an ultrafiltration membrane; Optionally, the ultrafiltration membrane includes any one or a combination of two or more of polyethersulfone ultrafiltration membrane, PVDF ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polysulfone ultrafiltration membrane, and nanocomposite ultrafiltration membrane; Optionally, the effective pore size of the ultrafiltration membrane is 5-100 nm.

7. An oil-soluble surfactant, characterized in that: Used in the preparation of polyester separation membrane in polyester composite membrane, the oil-soluble surfactant is dialkyl dimethyl ammonium salt.

8. The oil-soluble surfactant according to claim 7, characterized in that The dialkyldimethylammonium salt includes any one of dioctadecyldimethylammonium chloride, dioctadecyldimethylammonium bromide, dihexadecyldimethylammonium chloride, dihexadecyldimethylammonium bromide, didodecyldimethylammonium chloride, didodecyldimethylammonium bromide, and didecyldimethylammonium chloride, or a combination of two or more thereof.

9. A water-soluble surfactant, characterized in that: Used in the preparation of polyester separation membranes in polyester composite membranes, the water-soluble surfactant includes any one or a combination of two or more of amine salt surfactants, quaternary ammonium salt surfactants, heterocyclic surfactants, anionic sulfonate surfactants and carboxybetaine surfactants.

10. The water-soluble surfactant according to claim 9, characterized in that The amine salt type surfactant includes any one or a combination of two or more of n-octylamine, n-decylamine, n-dodecylamine, n-tetradecylamine, n-hexadecylamine and n-octadecylamine; Optionally, the quaternary ammonium salt surfactant includes any one of octaalkyltrimethylammonium chloride, octaalkyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, behenyltrimethylammonium chloride, and behenyltrimethylammonium bromide, or a combination of two or more thereof; Optionally, the anionic sulfonate surfactant includes any one or a combination of two or more of sodium dodecyl sulfonate, sodium hexadecyl sulfonate, sodium behenyl sulfonate, and sodium octane sulfonate; Optionally, the carboxy betaine surfactant includes any one of decyl betaine, cocamidopropyl betaine, lauryl amide propyl betaine, and carboxy betaine, or a combination of two or more thereof.

11. A polyhydroxy monomer, characterized in that Used in the preparation of polyester separation membranes in polyester composite membranes.

12. The polyhydroxy monomer according to claim 11, characterized in that The polyhydroxy monomer is any one or a combination of two or more of flavonol compounds, flavonoid compounds, catechol compounds, polysaccharide compounds and anthocyanin compounds.

13. The polyhydroxy monomer according to claim 12, characterized in that The chemical structural formula of the flavonol compound is: The chemical structural formula of the flavonoid compound is: The chemical structural formula of the catechol compound is: The chemical structural formula of the anthocyanin compound is: Wherein, R1 and R2 are both OH, and R3 is an arbitrary substituent.

14. The polyhydroxy monomer according to any one of claims 11 to 13, characterized in that The polyhydroxy monomer includes any one or a combination of two or more of tannic acid, protocatechuic acid, gallic acid, ellagic acid, anthocyanidin, proanthocyanidin, epigallocatechin gallate, epigallocatechin, gallocatechin, gallocatechin gallate, catechin, epicatechin, epicatechin gallate, quercetin, hesperidin, naringenin, daidzein, curcumin, anthocyanin, cyclodextrin, sodium alginate, and resveratrol.

15. The polyhydroxy monomer according to any one of claims 11 to 13, characterized in that The aqueous solution for preparing the polyester separation membrane comprises the polyhydroxy monomer and the water-soluble surfactant as described in any one of claims 9 to 10.

16. A method for preparing a polyester composite film, characterized in that: The steps include: Providing an aqueous phase solution containing a polyhydroxyl monomer and an oil phase solution containing a polyacyl chloride monomer; With the porous support membrane as the support interface, the polyhydroxy monomers in the aqueous solution and the polyacyl chloride monomers in the oil solution undergo interfacial polymerization at the water / oil interface, thereby preparing a polyester composite membrane.

17. The preparation method according to claim 16, characterized in that: The concentration of the polyhydroxy monomer in the aqueous phase solution is any value in the range of 0.5 g / L-15 g / L; Optionally, the concentration of the polyacyl chloride monomer in the oil phase solution is any value in the range of 0.5 g / L-30 g / L; Optionally, the oil phase solution further comprises an oil-soluble surfactant, and the concentration of the oil-soluble surfactant is any value in the range of 0.0001 g / L-100 g / L; Optionally, the aqueous phase solution further comprises a water-soluble surfactant, and the concentration of the water-soluble surfactant is any value in the range of 0.0001 g / L-100 g / L; Optionally, the method of using a porous support membrane as a support interface to allow polyhydroxy monomers in an aqueous solution and polyacyl chloride monomers in an oil phase solution to undergo interfacial polymerization at a water / oil interface to prepare a polyester composite membrane comprises the following steps: Under the conditions of a temperature of 15-40° C. and a relative humidity of 20-80%, applying the aqueous phase solution to the surface of the support film, leaving it for 10-300 seconds, then applying the oil phase solution and leaving it for 10-1800 seconds; The polyester composite film is prepared by annealing at 20-90°C for 5-30 minutes.

18. An application of a polyester composite film, characterized in that: It is used in seawater desalination, water treatment, chemical liquid treatment, concentration, hemodialysis, drug separation, food processing or environmental protection fields.

Citation Information

Cited By

  • Hesperidin-regulated polyamide nanofiltration membrane as well as preparation method and application thereof

    CN120900446A